No differences in FBN1 genotype between men with and without abdominal aortic aneurysm - Ida Åström Malm; Rachel De Basso; Peter Blomstrand (BMC Cardiovascular Disorders, 2023)
Abstract Background Abdominal aortic aneurysm (AAA) is an aortic enlargement in which the transverse diameter reaches at least 30 mm. Certain risk factors, such as age, male gender, and smoking, are well known; however, less is known about the genetic factors involved. Fibrillin-1 (FBN1) is a protein that coordinates the deposition of elastin fibres in the extracellular matrix and is therefore likely to affect the elastic properties in the aortic wall. Previously studies have found associations between the FBN1-2/3 genotype and arterial stiffness, but how different FBN1 genotypes, AAA, and arterial stiffness are related has been less frequently investigated. Aim This study aimed to investigate whether there is a difference in FBN1 genotype between men with and without AAA. A further aim was to study whether the FBN1 genotype affects arterial wall stiffness differently in men with and without AAA. Methods Pulse wave velocity and FBN1 genotyping were performed in 229 men (159 with AAA, 70 without AAA). Participants were recruited from ultrasound AAA surveillance programs or ongoing ultrasound screening programs from 2011 to 2016. Results The distribution of the FBN1 genotype in the AAA and control groups were as follows: FBN1-2/2: 62% vs. 64%; FBN1-2/3: 8% vs. 14%; and FBN1-2/4: 30% vs. 21%, respectively. Men with AAA and FBN1-2/2 had increased central pulse wave velocity (p < 0.005) compared to the control group (those without AAA) with the FBN1-2/2 genotype. Conclusion No differences were found with respect to FBN1 genotypes between men with and without AAA. The development of AAA in men does not appear to be linked to a specific FBN1 genotype. Nevertheless, men with FBN1-2/2 and AAA have increased central arterial stiffness compared to men with the same FBN1 genotype but without AAA.